Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s12034-013-0539-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimum synthesis conditions of nanometric Fe50Ni50 alloy formed by chemical reduction in aqueous solution

Abstract: In the present article, various nanometric Fe 50 Ni 50 alloys were synthesized by chemical reduction of the corresponding metal ions, with hydrazine in an aqueous solution. Process variables of reaction temperature, pH of the hydrazine solution and concentration of metal ions were varied in order to determine the optimum synthesis conditions regarding quality, productivity and cost. It is found that pH of hydrazine solution, at low concentration of metal ions, is the most crucial variable affecting the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This suggests that each spherical particle is nanostructured, i.e. it is composed of several nanocrystallites, as previously reported [9,18]. Based on XRD, EDS, and FE-SEM results, it is concluded that the chemically synthesized black particles are nc Fe 40 Ni 60 submicron-sized particles.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This suggests that each spherical particle is nanostructured, i.e. it is composed of several nanocrystallites, as previously reported [9,18]. Based on XRD, EDS, and FE-SEM results, it is concluded that the chemically synthesized black particles are nc Fe 40 Ni 60 submicron-sized particles.…”
Section: Resultssupporting
confidence: 78%
“…Characteristics of nc Fe 40 Ni 60 Particles Figure 1 shows the XRD pattern of the chemically synthesized particles. The four characteristic peaks for the disordered FCC g-Fe-Ni taenite phase 2h 5 44.05 , 51.3 , 75.6 , and 91.5 , marked by the Miller indices (111), (200), (220), and (311), respectively, are observed [9,18]. This reveals that the synthesized particles are pure Fe-Ni alloy.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The optimum synthesis parameters such as the reaction time, reduction temperature, reducing agent type, ratio of reducing agent to surfactant, and pH could be adjusted quickly to keep the nanoparticles' size and shape under control [38]. Researchers indicate that the reduction rate, crystallite, and particle sizes of the synthesized materials are mainly affected by the synthesis parameters [42]. Among the possibilities mentioned in the literature, most of the studies focused on the variations of the particle characteristics by changing the source material's concentration [43], hydrazine [44], and the surfactant [29].…”
mentioning
confidence: 99%
“…Therefore, additional efforts are needed to control experimental conditions for the synthesis of magnetic nanoparticles with controlled shape and size. FeNi 3 alloy nanoparticles were prepared by various methods such as: mechanical alloy [6,7], chemical reduction in solution [8,9], sol-gel combined with H 2 reduction [10], sol-gel autocombustion [11], sol-gel method [12], sol-gel route with benzyl alcohol [13], coprecipitation [14], chemical reduction based on the polyol process [15], reverse micelle technique [16], thermal decomposition of carbonyl compounds [17], hydrothermal reduction [18], to microwave assisted synthesis [19].…”
mentioning
confidence: 99%